INFLUENCE OF THE BOARD OF DIRECTORS, AUDIT COMMITTEE, MANAGERIAL OWNERSHIP AND INSTITUTIONAL OWNERSHIP ON FINANCIAL DISTRESS IN COMPANIES - Agusti, Anatia; Sriwijayanti, Hari; Khairi, Awalul (Jurnal Ipteks Terapan, 2023)
INFLUENCE OF THE BOARD OF DIRECTORS, AUDIT COMMITTEE, MANAGERIAL OWNERSHIP AND INSTITUTIONAL OWNERSHIP ON FINANCIAL DISTRESS IN COMPANIES